Analisis Faktor-Faktor yang Mempengaruhi Pembiayaan Musyarakah pada BPRS Investama Mega Bakti - Nurafifah Sahib (AT TAWAZUN: Jurnal Ekonomi Islam, 2025)
ABSTRACT The purpose of this study is to determine the influence of DPK, FDR and Dummy Covid on the allocation of musharakah financing at BPRS Investama Mega Bakti Makassar City. This research uses a quantitative method with a multiple linear regression method, analyzed using Eviews 12, the data used is the financial statements of BPRS Investama Mega Bakti for the 2020-2023 period obtained from the OJK website with a census sample technique. The results of the study show that partially deposits have a negative and significant effect on musharakah financing, FDR has a positive and insignificant effect on musharakah financing and Dummy Covid has a positive and significant effect on musharakah financing.Keywords: DPK, FDR, Covid 19, Musyarakah Financing, BPRS